Synthesis of Adenine Nucleosides by Transglycosylation using Two Sequential Nucleoside Phosphorylase‐Based Bioreactors with On‐Line Reaction Monitoring by using HPLC. Issue 24 (4th December 2017) - Cattaneo, Giulia; Rabuffetti, Marco; Speranza, Giovanna; Kupfer, Tom; Peters, Benjamin; Massolini, Gabriella; Ubiali, Daniela; Calleri, Enrica
Abstract: Uridine phosphorylase from Clostridium perfringens ( Cp UP, EC 2.4.2.3) was immobilized covalently in an aminopropylsilica monolithic column (25 mm×4.6 mm) upon functionalization with glutaraldehyde. Imino bonds that result from the reaction between the enzyme and the support were reduced chemically to afford a 66 % yield (13 mg) determined spectrophotometrically. The Cp UP immobilized enzyme reactor (IMER) was connected to a silica particle‐based IMER that contained a purine nucleoside phosphorylase from Aeromonas hydrophila ( Ah PNP, EC 2.4.2.1), which was developed previously and used successfully for the fast synthesis of some purine ribonucleosides by a "one‐enzyme" transglycosylation. Cp UP‐IMER and Ah PNP‐IMER were connected to a HPLC system by a six‐way switching valve. In this set‐up, the synthesis of 2′‐deoxyadenosine (dAdo, 8 ), adenosine (Ado, 9 ), and arabinosyladenine (araA, 10 ) by a "two‐enzyme" transglycosylation is coupled directly to on‐line reaction monitoring. Under the optimized transglycosylation conditions (2:1 ratio sugar donor/base acceptor; 10 mm phosphate buffer; pH 7.25; temperature 37 °C, flow rate 0.1 mL min −1 ), defined by a 2 (5‐2) III experimental design, the conversion of dAdo and Ado was approximately 90 %, and araA was synthesized in 20 % yield. Abstract : All together now ! Uridine phosphorylase from Clostridium perfringens ( Cp UP) is immobilized covalently in an aminopropylsilica monolithic column. The Cp UP immobilized enzyme reactor (IMER) is connected to a silica‐particle‐based IMER that contains a purine nucleoside phosphorylase from Aeromonas hydrophila ( Ah PNP). The Cp UP‐IMER and Ah PNP‐IMER are used to synthesize 2′‐deoxyadenosine, adenosine, and arabinosyladenine by a "two‐enzyme" transglycosylation.